Acupoint catgut embedding: a potential intervention strategy for obesity-related precocious puberty - Liang, Yun; Yuan, Yuan; Yang, Jie (Frontiers in Endocrinology, 2024)
Obesity-related precocious puberty is triggered by obesity, and acupoint catgut embedding (ACE) therapy is known to treat obesity. The purpose of this study is to validate the theoretical hypothesis that ACE may have potential effects in delaying the onset of obesity-related precocious puberty. Sprague-Dawley female rats at 21 days postnatal were randomly assigned to three groups: one group receiving a high-fat diet with ACE, another group receiving a high-fat diet only (HFD), and a baseline control group fed a normal chow diet (NCD), with 8 animals per group. The timing of vaginal opening (VO) was monitored, and serum levels of luteinizing hormone (LH), folliclestimulating hormone (FSH), and total estradiol (E2) were assessed, followed by statistical analysis. The Kaplan-Meier survival curves, with VO as the endpoint, demonstrated that the rats in the ACE group experienced a delayed vaginal opening compared to those in the HFD group, with statistically significant differences. The levels of FSH, LH, and E2 indicated that the sexual development process in the ACE group's rats was delayed in comparison to the HFD group. This study confirms that the therapeutic intervention of ACE for obesity exerts a potential role in delaying the onset of obesityrelated precocious puberty.